Using text types in creating tasks that develop listening comprehension skills - Rakhmatullayeva , Nargiza (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article discusses the issues of effective use of text types in creating tasks that develop listening comprehension skills. The role of narrative, descriptive, explanatory and evaluative texts in the listening comprehension process and their impact on the speech and cognitive development of students are analyzed. It also shows ways to develop tasks based on different text types, adapt them to the age and individual characteristics of students, and form the skills of understanding, analyzing and re-expressing the information heard. The article also provides methodological recommendations aimed at increasing the effectiveness of tasks based on text.